HOW BRAND IMAGE AND PERCIEVED PRICE AFFECTING CUSTOMERS’ BUYING DECISION : A PLS-SEM ANALYSIS - Mardiana, Siti; Yudawisastra, Helin Garlinia; Amin, Neneng Nurbaeti; Rafli, Rizal (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
The purpose of this study was to test the influence model of brand image perception and pricing policy perception on customer purchasing decisions. The brand used as the object of the study was Citra Body Lotion and the respondents were students because the Citra brand is associated with a group of young female customers. The research method used was a quantitative method with PLS-SEM analysis using the SmartPLS application. A total of 125 data from students were successfully collected. The results of the analysis showed that the measurements used in the questionnaire met all the requirements as a good measurement model. Meanwhile, the results of the model structure analysis showed an R2 value = 0.889, which means that 88.9% of the variance in the endogenous variables (Actual Buying Decision) can be substantially predicted by the exogenous variables (Brand Image and Pricing Policy). The Q2 value shows a figure of 0.347, which means that the exogenous variables in the model are able to predict endogenous variables with a moderate to high level of accuracy. Research limitations and implications are discussed in the discussion and conclusion sections.